Observation of vinylidene emission in mixed phosphine/diimine complexes of Ru(II) at room temperature in solution - Bogado, André Luiz; Rominger, Frank (Journal of organometallic chemistry, 2012)
The mixed ruthenium(II) complexes trans-[RuCl2(PPh3)2(bipy)] (1), trans-[RuCl2(PPh3)2(Me2bipy)](2), cis-[RuCl2(dcype)(bipy)](3), cis-[RuCl2(dcype)(Me2bipy)](4) (PPh3 = triphenylphosphine, dcype = 1,2-bis(dicyclohexylphosphino)ethane, bipy = 2,2′-bipyridine, Me2bipy = 4,4′-dimethyl-2,2′-bipyridine) were used as precursors to synthesize the associated vinylidene complexes. The complexes [RuCl(CCHPh)(PPh3)2(bipy)]PF6 (5), [RuCl(CCHPh)(PPh3)2(Me2bipy)]PF6 (6), [RuCl(CCHPh)(dcype)(bipy)]PF6 (7), [RuCl(CCHPh)(dcype)(bipy)]PF6 (8) were characterized and their spectral, electrochemical, photochemical and photophysical properties were examined. The emission assigned to the π-π∗ excited state from the vinylidene ligand is irradiation wavelength (340, 400, 430 nm) and solvent (CH2Cl2, CH3CN, EtOH/MeOH) dependent. The cyclic voltammograms of (6) and (7) show a reversible metal oxidation peak and two successive ligand reductions in the +1.5-(−0.64) V range. The reduction of the vinylidene leads to the formation of the acetylide complex, but due the hydrogen abstraction the process is irreversible. The studies described here suggest that for practical applications such as functional materials, nonlinear optics, building blocks and supramolecular photochemistry.
Available online 29 September 2011
Gesehen am 09.10.2018